3D printed nanofiltration membrane technology for waste water distillation. (October 2022) - Khan, Sadaf Bashir; Irfan, Syed; Lam, Su Shiung; Sun, Xiaohong; Chen, Shenggui
Abstract: Surface water supply provides the vast majority of the world's drinkable water, however, surface water may contain a broad variety of pollutants originated from various sources, such as households, industry, and agriculture. As a result, it is critical to achieve acceptable water quality while also reducing the organic and inorganic impurities. Potable water production methods have been developed and tested in various ways. It is possible to manufacture high-quality drinking water using nanofiltration (NF) membranes. In contrast, fouling has remained the most significant barrier to membrane technology advancement. Renewable energy sources may decrease the extra energy needed by a membrane with tiny holes. Recent years have seen a significant increase in interest in three-dimensional printing (3D printing [3D-P]). Surface imprinting technologies, in general, have not yet reached the maturity stage of development, notably in membrane design and production. It is discussed in this review article how different 3D printing technologies are now accessible, how they relate to current breakthroughs in the area, and how they may be used to fabricate nanosheets, module spacers, or thin layers design for water purification as well as potential applications of surface imprinting in the near future. It is anticipated that the revolutionary synthesis of novel membrane module components will occur in the near future due to recent breakthroughs in 3D-P technology. It is predicted that 3D-P technologies would create a broader range of membrane module components with improved efficacy and efficiency due to speed, materials, and resolution improvements. Water purification methods comprising membrane separation are potential applications that might benefit from surface imprinting patterns with complicated topography in the future for water purification among them. Graphical abstract: Unlabelled Image Highlights: Recent years have significantly increased interest in three-dimensional printing (3D printing [3D-P]). This study explores 3D printing to create nanosheets, spacers, or thin layers for water purification and surface imprinting. The advancements in 3D-P technology could lead to the revolutionary synthesis of novel membrane module components. Surface imprinting patterns with complex topography may assist water purification procedures involving membrane separation. Surface imprinting technology has not yet reached maturity stage of development, notably in membrane design and production.